Unmet Needs in Managing Myocardial Infarction in Patients With Malignancy - Inohara, Taku; Endo, Ayaka; Melloni, Chiara (Frontiers in Cardiovascular Medicine, 2019)
Patients with cancer face a high short-term risk of arterial thromboembolism. One of the most fatal manifestations of arterial thromboembolism is myocardial infarction (MI), and patients with cancer face a 3-fold greater risk of MI than patients without cancer. The individual risk for arterial thrombotic events in patients with cancer is determined by the complex interaction of baseline cardiovascular risk factors, cancer type and stage, chemotherapeutic regimen, and other general contributing factors for thrombosis. Managing MI in patients with cancer is a clinical challenge, particularly due to cancer’s unique pathophysiology, which makes it difficult to balance thrombotic and bleeding risks in this specific patient population. When patients with cancer present with MI, a limited proportion are treated with guideline-recommended therapy, such as antiplatelet therapy or invasive revascularization. Despite the limited evidence, existing reports consistently suggest similar clinical benefits of guideline-recommended therapy when administered to patients with cancer presenting with MI. In this review, we briefly summarize the available evidence, clinical challenges, and future perspectives on simultaneous management of MI and cancer, with a focus on invasive strategy.